The Effects of an Evaporative Cooling System on Reducing Heat Load in Lactating Dairy Cows - J. R. Johnson; M. J. Wolf; J. McBride; Michael Brouk (Kansas Agricultural Experiment Station Research Reports, 2017)
This study was conducted to evaluate the effect of 2 cooling systems on barn temperature, core body temperature (CBT), respiration rate, rear udder temperature, and lying time in lactating Holstein dairy cows. Twenty lactating Holstein dairy cows were randomly assigned to 1 of 2 treatment groups: CONV, where cows were housed in a conventional, open-sidewall freestall barn equipped with feedline soakers and fans located over the feedline and stalls; and TUNNEL, where cows were housed in a tunnel-ventilated freestall barn utilizing an evaporative cooling system. TUNNEL was effective at reducing barn temperature humidity index (THI) compared to CONV, but failed to alter CBT (101.5 ± 0.04°F). TUNNEL cows had reduced respiration rates (52.0 vs. 57.9 ± 2.2 breaths per minute) and skin temperatures (91.8 vs. 94.1 ± 0.6°F) compared to CONV, while TUNNEL cows had increased lying time by 1 hour per day (11.8 vs. 10.8 ± 0.3 hours per day). Overall, the evaporative cooling system (TUNNEL) was effective in reducing barn THI leading to reduced respiration rates and rear udder temperatures and increased daily lying time. No treatment differences were detected for CBT, however, likely a result of the cooler ambient conditions under which the study took place.
Keywords: heat stress; evaporative cooling; core body temperature; lying behavior